A novel mutation in the ABCD1 gene of a Chinese patient with X-linked adrenoleukodystrophy: Case report. Issue 21 (May 2018) - Wang, Jing; Zhu, Qian; Liu, Hongqian
Abstract: Rationale: X-linked adrenoleukodystrophy (X-ALD) is the most common peroxisomal disorder, which is inherited as an X-linked recessive trait. ATP binding cassette subfamily D member 1 (ABCD1) localized to Xq28 is the only gene associated with ALD. Patient concerns: We report a case of Chinese boy with childhood cerebral ALD, who began experiencing symptoms at the age of 5 years and 2 months. Very long chain fatty acids analysis revealed high levels of C24/C22 ratio and C26/C22 ratio in the plasma. Magnetic resonance imaging (MRI) showed abnormal bilateral white matter lesions in brainstem, temporal, occipital, and parietal lobes. Diagnoses: Direct sequencing of the ABCD1 gene identified a novel c.1502del mutation on exon 6, which causes a substitution of the 501st amino acid from methionine to serine and finally the 557th codon is changed to stop codon. Interventions: Special education and rehabilitation therapy. Outcomes: The disease progressed rapidly and resulted in death at the age of 8 years. Lessons: Early detection of mutations in the ABCD1 gene may facilitate diagnosis, genetic counseling and potentially aid prenatal diagnosis of the disease.